Transforming family farming: Advancing inclusive digitalization in the Amazon - Oliveira, Denis; Laurens, Violaine (2025)
KEY MESSAGES ◼ The climate crisis threatens the stability of Brazil’s agri-food systems—putting global food security at risk. As a major food producer, Brazil must urgently adopt locally tailored technologies that boost resilience to climate change and improve conditions for family farmers in vulnerable rural areas. ◼ The ageing rural population in Brazil and Latin America is closely linked to declining agricultural productivity and worsening socio-economic conditions. As young people migrate to urban areas seeking better opportunities, the rural labor force weakens. While older farmers bring valuable experience, limited long-term planning often restricts the adoption of new technologies. ◼ The agroecological production model faces major barriers to widespread adoption in Brazil. The country’s vast cultural diversity demands tailored technologies adapted to local realities. Meanwhile, the entrenched large-scale model—relying heavily on chemical inputs and machinery—remains the dominant agricultural approach, making the shift to alternatives difficult. ◼ Digital tools for farmer advisory services are rapidly expanding. Yet, they often neglect local realities and the specific needs of small-scale family farmers, focusing instead on the demands of international markets for large-scale, standardized, low-cost production to feed global value chains. ◼ The results of the Inclusive Digital Tools (ATDT) project in Brazil suggest that participatory approaches can be an effective way to adapt digital technologies, helping farmers access knowledge and make better decisions. The co-creation of technical knowledge is important to accelerate the dissemination of more efficient and resilient production techniques.